(untitled) (American Journal of Islam and Society, 2014)
There has rarely been a dull period in Lebanon’s post-Ottoman political history. Its central geographic, if not political, position within the Arab region, along with its penetrable political system, has made the country vulnerable to regional and international pressures. These pressures have manifested themselves in both spectacular (e.g., the civil war and Israeli occupation) and more subtle ways (e.g., the sustained brain drain and continued socioeconomic deprivation of rural communities). Despite these changes, however, the country’s political system has remained resilient and the sectarian power-sharing system 104 The American Journal of Islamic Social Sciences 31:2 forming the core of national politics and distribution of (formal and informal) political power has changed only in style, not substance. Rola el-Husseini’s inquiry into the country’s political elite background, structure, politics, recruitment patterns, and discourses is layered against the resiliency of its confessional system. Her core concern is to trace the Lebanese elite’s interactions and their major structural determinants. As such, the inquiry has to ask how the period of Syrian control – Pax Syriana – created new possibilities and limitations for elite politics in Lebanon. Thus, while the text is rich in historical analysis and sound in its treatment of Lebanon’s postcolonial politics, the main period of focus is on 1991 to 2005, when Syrian influence was at its peak. As one would expect, Syria’s influence on elite recruitment and this class’ politics and discourses was profound during this period ...